Paleogene-Neogene ring-shaped sedimentary system and reservoir characteristics in the Western depression of the Qaidam Basin - Liu, Guoyong; Xue, Jianqin; Wu, Kunyu; Wu, Songtao; Zhang, Boce; Liu, Zhanguo; Xing, Haoting (Frontiers in Earth Science, 2024)
The Paleogene-Neogene strata in the Western Depression of the Qaidam Basin represent a primary focus for oil and gas exploration and development.Influenced by both terrigenous clastic influx and endogenic carbonate deposition, these strata exhibit significant variation in sedimentary systems and reservoir characteristics. This study comprehensively examines the depositional patterns and reservoir properties of the Paleogene-Neogene sequence across the inner, middle, and outer belts of the basin, employing core analysis, thin section petrography, and physical property assessment of reservoirs. Key findings include (1) The development of a concentric sedimentary system in the Western Depression during the Paleogene-Neogene period, characterized by increased carbonate mineral content and decreased clastic material from the periphery to the center of the basin. (2) Varied sedimentary facies associations across different zones, with the outer belt dominated by fan delta and braided river delta deposits, and the middle and inner belts characterized by near-shore shallow lacustrine carbonates and algal mat deposits, and offshore semi-to deep-lacustrine fine sediments, respectively. (3) The outer belt exhibits reservoirs with favorable physical properties and connectivity, while the inner and middle belts show high heterogeneity, indicating potential for lithological traps and shale oil exploration. These insights offer scientific guidance for further investigation into the depositional systems of lacustrine basins in the Western Depression of the Qaidam Basin and for identifying promising reservoirs.